Current Snapshots on Stroke Prevention and Control and More Proactive National Strategies Against It in China - Bin Jiang (Journal of Central Nervous System Disease)
Background and Purpose Stroke has become a major public health problem. This paper aims to briefly review the current epidemiological characteristics, preliminary achievements, and national action strategies related to stroke prevention and control in China. Methods English and Chinese literature were searched on stroke epidemiological characteristics and more proactive strategies for its prevention and control in China. Potential papers related to this topic were identified from PubMed, Medline, Embase, Cochrane Library, Wanfang Database, SINOMED, and China National Knowledge Infrastructure databases, as well as the annual reports and websites of the People’s Daily, the State Council, and the National Health Commission of the People’s Republic of China. Results Stroke has been ranked among the top three causes of death in China, and has become a public health problem endangering people’s health. High rates of incidence, mortality, and disability bring a heavy burden to stroke patients, families, and society. With China’s economic development, urbanization, and population aging, the prevalence and incidence of stroke are still rising. Although some progress has been made in specialized stroke prevention and treatment in China, there is still much room for improvement. Curbing increasing stroke due to increased prevalence and suboptimal control of risk factors and unhealthy lifestyles is no longer just the efforts of medical service institutions. It still requires a more proactive national strategy and general mobilization of the whole people. Increased prevalence of stroke, survivors’ unfavorable outcomes, and suboptimal rehabilitation also need specialized stroke care and the perfect Hierarchical Medical System within the regional medical consortium in China. Conclusions The current situation of stroke prevention and treatment is still very serious in China. In the future, the stroke prevention and treatment model will change from passive stroke treatment and risk factor control to a more proactive prevention model of health factor management.